"Integrasi Pendidikan Islam dalam Program Pendidikan Guru Sekolah Dasar: Tinjauan Literatur" - Kurniawanto, Eko (SISTEMA: Jurnal Pendidikan, 2024)
This study aims to analyze the integration of Islamic education in elementary school teacher education programs through a literature review. In the context of globalization and modernization, religious education plays a crucial role in shaping the character and morals of students. The Elementary School Teacher Education (PGSD) program is expected to produce graduates who not only have high academic competence but also possess strong character in accordance with Islamic values. The research method used is library research, which involves analyzing various relevant literature sources, including books, journals, articles, and educational policy documents. This study identifies several important aspects in the integration of Islamic education, such as curriculum, teaching methods, the role of teachers, and evaluation.The results of the study indicate that the integration of Islamic education in the PGSD program can be carried out through several approaches, such as comprehensive curriculum development, continuous teacher training, and holistic assessment. Additionally, the role of teachers as role models is very important in internalizing Islamic values to students. Challenges faced include limited resources, resistance to change, and the gap between theory and practice. Thus, this study concludes that the integration of Islamic education in the PGSD program requires synergistic cooperation between various parties, including the government, educational institutions, teachers, and the community. This effort is expected to shape the next generation that is not only intellectually smart but also has good character and noble morals. Keywords: Integration of Islamic education, teacher education program, elementary school, literature review, character, curriculum.